1999
DOI: 10.1002/(sici)1097-4601(1999)31:8<539::aid-kin3>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Studies on toluidine blue reaction with sulfite in aqueous solution and role of Cu(II) as promoter

Abstract: The kinetic and mechanistic details of the reaction between toluidine blue and sulfite were studied spectrophotometrically by monitoring the depletion of toluidine blue at 633 nm. The reaction had first-order dependence on both the reactants, a stoichiometric ratio of 1:1 and a negative salt effect indicating the participation of TB ϩ and SO 3 2Ϫ ions in the ratelimiting step. The reaction products were leuco base of toluidine blue and sulfate. The reaction was pH dependent and hence studied at its optimum pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Also, for SBA‐15 silica a significant increase in TBO adsorption is observed at a pH value of 6. This is due to at pH values higher than 6, the TBO is clearly positively charged (pK a = 7.2) favoring the electrostatic interaction between dye and adsorbent . On the other hand, the slightly decrease in dye adsorption for MCF at high pH could be attributed to the competition between OH − ions and negatively charged mesoporous silica .…”
Section: Resultsmentioning
confidence: 96%
“…Also, for SBA‐15 silica a significant increase in TBO adsorption is observed at a pH value of 6. This is due to at pH values higher than 6, the TBO is clearly positively charged (pK a = 7.2) favoring the electrostatic interaction between dye and adsorbent . On the other hand, the slightly decrease in dye adsorption for MCF at high pH could be attributed to the competition between OH − ions and negatively charged mesoporous silica .…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, the proposed mechanism is clearly supported by a kinetic study based on the reaction of TB + with sulte at pH 7.2, in which Cu 2+ ions play an active role as a promoter or catalytic activator. 35 In the relevant kinetic study, it was also observed that Cu-TB, Cu-sulte and Cu-TB-sulte species based on binary and ternary interactions have complex formation constants of 7.168, 6.367 and 14.291 with a standard deviation ranging from 0.003 to 0.008 at pH 7.2. Thus, for further studies, the different analytical variables affecting CPE efficiency were optimized in order to achieve the maximum sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the reduction of TB + or TBH 2+ by ascorbic acid at 600 nm was used for the kinetic determination of ascorbic acid in fruits and vegetables in linear ranges of 3-35 and 5-50 mg L −1 by slope or fixed-time and variable time methods, respectively [48]. Similarly, it is seen that Cu 2+ ion as soft metal ion selectively enhances the rate of reaction between TB + (or TBH 2+ ) and SO 3 2− at 633 nm by forming a ternary complex with a stability constant of logK f : 14.291 with standard deviation of 0.007 at pH 7.2 [49].…”
Section: Resultsmentioning
confidence: 99%